An overview of biomedical implants : biomaterials for the human body - Shokuhfar, Tolou (John Wiley & Sons, Inc., 2025)
"Biomaterials form the backbone of many major biomedical implants. They encompass everything from the more traditional biomaterials used in implants such as metals and metal alloys used in orthopedic surgeries (e.g., prosthetic hip and knee joints); devices for the cardiovascular system (e.g., stents; heart valves; pacemakers); dental implants and restorations; polymers for ocular implants (e.g., intraocular lens) as well as emerging biomaterials used in next generation of the implants mentioned above, nanobiomaterials for regenerative implants and even drug delivery implants. Currently estimated at approximately $100 billion annually in the US alone, the implant industry is estimated to grow considerably with an aging population and the demand for improved healthcare worldwide. Scientists and engineers involved in research and development efforts in the biomedical industry often wish to broaden their background in implant biomaterials. Consequently, there is a recognized demand for appropriate books in the area of biomaterials implants. However there are no comprehensive book available that describes both traditional and advanced next generation biomaterials for all types of implants currently used in human body"-- Provided by publisher.
Keywords: Implants, Artificial -- Biocompatibility.; Biomedical materials.; elektronické knihy; electronic books